2017
DOI: 10.18535/jmscr/v5i12.26
|View full text |Cite
|
Sign up to set email alerts
|

Our Experience on Vaginal Discharge in Reproductive Age Groups Causing By Microorganisms in a Tertiary Care Indian Teaching Hospital

Abstract: Ostetrics and Gynaecology, IMS and SUM hospital, Bhubaneswar, between September 2012 and September 2014. A total of 100 women in the reproductive age group who had symptoms of vaginitis were examined. Data were coded and analyzed. Results: Out of the 100 patients examined, 77 (77%) cases were organism positive. Among the positive cases, BV (27%) was the most common microbiological cause of abnormal vaginal discharge, followed by trichomoniasis (25%), vaginal candidiasis (22%), combined infection (Candida and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In terms of personal hygiene, as has been tradition in the community, which had been repeatedly objected to in view of sufficient water supply and reasonable purchasing power and its repercussion in terms of helminth infestation, skin pathologies, transmission of faeco-oral disease and deterioration of general health, the practice of taking bath on alternate days was seen in 106 (30.3%) subjects (Table 3). 4 While in the study conducted by Varsha Chaudhary et al in Northern India the discharge was found to increase with increase in age and was more among women aged 43-49 years (59.1%). 5 Based on religion and considering the demographic characteristics of study area, which for last 5 decades was populated by Muslims from southern states of Tamil Nadu and Andhra Pradesh, 259 (74.0%) were Muslims and 89 (25.4%) were Hindus.…”
Section: Resultsmentioning
confidence: 89%
“…In terms of personal hygiene, as has been tradition in the community, which had been repeatedly objected to in view of sufficient water supply and reasonable purchasing power and its repercussion in terms of helminth infestation, skin pathologies, transmission of faeco-oral disease and deterioration of general health, the practice of taking bath on alternate days was seen in 106 (30.3%) subjects (Table 3). 4 While in the study conducted by Varsha Chaudhary et al in Northern India the discharge was found to increase with increase in age and was more among women aged 43-49 years (59.1%). 5 Based on religion and considering the demographic characteristics of study area, which for last 5 decades was populated by Muslims from southern states of Tamil Nadu and Andhra Pradesh, 259 (74.0%) were Muslims and 89 (25.4%) were Hindus.…”
Section: Resultsmentioning
confidence: 89%